Analisis Komparatif Pendapatan Usahatani Kentang, Kubis, Dan Brokoli Di Desa Kenalan Kecamatan Pakis Kabupaten Magelang - Pantja Siwi V R Ingesti; Bahrul Ulum (Universitas Tidar, 2026)
This study aims to analyze differences in income from potato, cabbage, and broccoli farming in Kenalan Village, Pakis District, Magelang Regency. The study was conducted in 2024 using a census survey method with 40 farmer petanits: 20 potato farmers, 10 cabbage farmers, and 10 broccoli farmers. Data analysis was conducted using farm income analysis, business feasibility analysis (R/C Ratio), normality test, homogeneity test, analysis of variance (ANOVA), and Games-Howell follow-up test. The results showed that potato farming provided the highest income, with a range of Rp23,525,357.14–Rp76,608,673.47 per hectare, with an R/C Ratio of 1.41–2.29. Broccoli farming generated income of Rp18,674,315.79–Rp27,823,389.36 per hectare, with an R/C Ratio of 1.62–2.81. Meanwhile, cabbage farming generated income of Rp11,275,291.67–Rp24,059,226.19 per hectare with an R/C Ratio of 1.27–1.75. The results of the normality test showed that the data were normally distributed (p0.05). The ANOVA results showed a significant difference in income between farming groups (F = 10.038; p = 0.000). Further Games-Howell tests showed that potato farming income was significantly different from broccoli farming (p = 0.001) and cabbage farming (p = 0.000), while broccoli and cabbage farming income were not significantly different (p = 0.868). The results showed that potato farming was the commodity that provided the highest income compared to cabbage and broccoli at the research location.